[Wickford Mill, Longford, Tasmania] - Glover, John Richardson, 1790-1868. (1850)
Henry Clayton of Wickford "had other ventures, including a flour mill ... at Longford". Ref.: Early houses of Northern Tasmania / E. Graeme Robertson and Edith Craig, Melbourne, Georgian House, 1964, v. 1, p. 140.
Title devised by cataloguer.
Condition: Good; detached from album.
Part of the collection: Sketchbook of properties in the Longford region of Tasmania.
Part of panorama extending over 2 pages of album: sketch (a), line sketch, ink and wash (unfinished); sketch (b), ink and wash.
Also available online
Keywords: Wickford Mill (Tas.) -- Pictorial works; Flour mills -- Tasmania -- Longford -- Pictorial works; Architecture, Colonial -- Tasmania -- Longford -- Pictorial works; Longford (Tas.) -- Buildings, structures, etc -- Pictorial works